Prevalence of gastrointestinal parasites in captive exotic birds at central zoo, Bagmati, Nepal - Bohara, Ashok; Chokhal, Keshab; Singh, Ankit Kumar; Gupta, Ranjana (Journal of Agriculture and Natural Resources, 2025)
Gastrointestinal (GI) parasitic infection is among the major health problems affecting captive exotic birds, leading to poor growth, reduced reproductive performance, and even mortality. Central Zoo, Nepal, serves as a form of ex-situ conservation, and this study aimed to determine the general prevalence of helminth and protozoan gastrointestinal parasites in 16 different species of exotic avian fauna. Freshly defecated fecal samples were collected from 100 individuals, with five to ten individuals per species. We used iodine wet mount, flotation, and sedimentation methods to detect the protozoan and helminth samples, where five genera of parasites were detected at a 54% prevalence rate.  The study results were that one protozoan genus, Eimeria sp. (37%), and four helminth genera. Among them, Ascaridia sp. (23%) showed the highest prevalence, followed by Codiostomum sp. (3%), Trichostrongylus sp. (10%), and Strongyloides sp. (7%). The prevalence of protozoan parasites (57) was higher than that of helminth parasites (43), and the difference was statistically insignificant (χ² = 0.197, p = 0.656). Similarly, the difference in prevalence between single and mixed infections was found to be statistically significant (χ² = 4.481, p = 0.034). The prevalence of protozoan parasites (57) was higher than that of helminth parasites (43), and the difference was statistically insignificant (χ² = 0.197, p = 0.656). Similarly, the difference in prevalence between single and mixed infections was found to be statistically significant (χ² = 4.481, p = 0.034). Double infections were the highest occurrence (76.19%) compared to the multiple infections (23.80%) among the mixed infections. Evidence-based deworming protocols were recommended to enhance healthy captive avian populations.